2008
DOI: 10.1111/j.1365-2826.2008.01747.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen Influences on Mitochondrial Gene Expression and Respiratory Chain Activity in Cortical and Mesencephalic Astrocytes

Abstract: The regulation of mitochondrial energy metabolism plays an essential role in the central nervous system (CNS). Abnormalities of the mitochondrial respiratory chain often accompany neurodegenerative diseases. This makes mitochondria a perfect target for strategies of cellular protection against toxic compounds and pathological conditions. Steroid hormones, such as oestrogen, are well-known to fulfil a protective role in the brain during ischaemic and degenerative processes. Because astrocytes function as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 71 publications
(98 reference statements)
0
23
0
Order By: Relevance
“…In recent studies, we and others have shown that E promotes the expression of mitochondria-encoded subunits of the respiratory chain, thereby influencing mitochondrial respiratory activity and enhancing functional efficiency (Araú jo et al 2008, Irwin et al 2008. Mitochondrial functions are not only affected by regulation of nuclear and mitochondrial gene expression and activity of the respiratory chain (Zheng & Ramirez 1999, Araú jo et al 2008, Irwin et al 2008), but K7 M E or P for 24 h. Antagonists of estrogen and progesterone receptors (ICI and Rti respectively) were added simultaneously to the respective steroid hormone treatment. Specific quantification of fusion genes, Mfn1 (A and C; grey columns) and Mfn2 (A and C; black columns), and fission genes, Dnm1l (B and D; grey columns) and Fis1 (B and D; black columns), was performed by RT-PCR.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In recent studies, we and others have shown that E promotes the expression of mitochondria-encoded subunits of the respiratory chain, thereby influencing mitochondrial respiratory activity and enhancing functional efficiency (Araú jo et al 2008, Irwin et al 2008. Mitochondrial functions are not only affected by regulation of nuclear and mitochondrial gene expression and activity of the respiratory chain (Zheng & Ramirez 1999, Araú jo et al 2008, Irwin et al 2008), but K7 M E or P for 24 h. Antagonists of estrogen and progesterone receptors (ICI and Rti respectively) were added simultaneously to the respective steroid hormone treatment. Specific quantification of fusion genes, Mfn1 (A and C; grey columns) and Mfn2 (A and C; black columns), and fission genes, Dnm1l (B and D; grey columns) and Fis1 (B and D; black columns), was performed by RT-PCR.…”
Section: Discussionmentioning
confidence: 96%
“…Cultured cortical astrocytes were treated with E concentrations known to be effective in the brain (Luconi et al 1999, Ivanova et al 2001, Pawlak et al 2005, von Schassen et al 2006, Araú jo et al 2008. Under basal (physiological) conditions, cultured cortical astrocytes from males and females did not differ in their characteristics for mitochondria morphology and cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…In another project, we have investigated the influence on the transcription levels of mitochondrial DNA in cortical astrocytes and demonstrated that estrogen is capable of promoting transcriptional activity by approx. 50% [68]. Although there is still uncertainty of attributing these effects to direct estrogen-mitochondrion interactions, the chosen experimental approach in these experiments by using isolated mitochondria is in support for this view.…”
Section: Regulation Of Mitochondrial Structural Organization By Estrogenmentioning
confidence: 93%
“…Consistent with the increased gene expression is the increased respiratory control ratio, elevated complex IV activity, in association with simultaneous reduction of free radical generation in brain. Araújo et al [117] examined E 2 effects on MRC gene expression and the MRC activity of rat cortical and mesencephalic astrocytes. They observed that MRC structural and functional properties were regulated dependent on the E 2 exposure time and the brain region, but independent of the nuclear ERs.…”
Section: Regulation Of Ndna-encoded Mrc Proteins By E2 Via Nrfsmentioning
confidence: 99%